Narcissism, femininity and alienation - Bartky, Sandra Lee (Social Theory and Practice, 1982)
Keywords: amériques; cours; discipline; fem1000; féminisme marxiste; philosophie politique; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sexualité; thématiques; états-unis

Production du sentiment amoureux et travail des femmes - Dayan-Herzbrun, Sonia (Cahiers Internationaux de Sociologie, 1982)
Il est important d'expliciter le rapport qui relie le vécu privé des femmes à leur vie professionnelle, et, sous la dépendance matérielle, de faire surgir la dépendance affective. Celle-ci est liée aux positions dissymétriques occupées par les hommes et les femmes dans la relation amoureuse, qui sont une des marques sociales de la différenciation sexuelle dans la société moderne
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem9000; inégalités; ressource en ligne; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail

Conceptualisation des femmes - Edholm, Felicity; Harris, Olivia; Young, Kate (Nouvelles Questions Féministes, 1982)
Cet article présente une synthèse critique des concepts et théories ethnographiques qui prétendent expliquer la subordination des femmes dans la société. Mais cette tentative de conceptualisation des femmes se heurte au manque de rigueur et à l'ambiguïté des termes employés par Meillassoux, Engels, Balibar, etc. qui se servent des modèles d'évolution sociale simplifiés utilisant une catégorie «femme» a-historique. Pour mener à bien cette réflexion sur le domaine des femmes et la division sexuelle du travail, les auteurs de l'article procèdent à la critique de tout l'appareil idéologique dans lequel se sont effectuées ces analyses.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem9000; rapports sociaux de sexe; ressource en ligne; sciences humaines; sociologie

The daughter's seduction: Feminism and psychoanalysis - Gallop, Jane (Cornell University Press, 1982)
At the time this book was published in 1982, Jane Gallop was professor of French at Miami University; she has also written Intersections: A Reading of Sade with Bataille, Blanchot, and Klossowski. She wrote in the Introduction, "[the book] studies the relation between contemporary feminist theory and the psychoanalysis of Jacques Lacan... it enters into a network of problems: problems of sexual difference, of desire, of reading, or writing, of power, of family, of phallocentrism and of language... this book is ... a contribution to the sort of thinking it describes---that is, a contribution to French psychoanalytic feminist thought from the vantage point of these English-speaking shores." (p.11) She adds, "The book begins by calling into question certain feminist assumptions through the agency of Lacanian psychoanalysis. It ends by calling into question certain psychoanalytic positions through the agency of feminist writing." (p.15) She states that "[Freudian] Phallocentrism seems wrong to [Ernest] Jones: that is, immoral by virtue of being 'excessive, immoderate,' which is to say, unreconcilable with a 'sense of proportion.' The phallic disproportion brings him... to champion the claims of an 'underestimated' female sexuality to a more balanced, more proportionate estimate. His 'sense of proportion,' his spirit of fair play, will be sufficiently scandalized to provoke his only major departure from Freud's theory." (p. 16) She observes that in an article, "[Stephen] Heath begins by informing us that ... Lacan's 1972/73 seminar [is] devoted to 'what Freud expressly left aside... What does woman want?' ... Yet Lacan said nothing of devotion... Lacan speaks of a beginning... of a relation to this question: far from devoting himself to women he is simply at the stage of approach, first and rather aggressive encounter." (p. 43) This book will be of interest to feminists studying psychoanalysis, or to students of Lacan.
Keywords: 1900-1999; amériques; cours; discipline; fem1000; premier cycle; psychanalyse; périodes historiques; régions géographiques; sciences; sciences humaines; thématiques; écriture des femmes*; états-unis